Generative artificial intelligence and its implications for labor markets in developing countries: a review essay - Cruces, Guillermo Antonio (2024)
The unprecedented developments in artificial intelligence technology and its recent widespread availability hold transformative potential to reshape global economic dynamics and labor markets, though opinions on its effects vary greatly. Transformative or not, the irruption of AI has sparked ample public discussion as well as the rapid development of theoretical and empirical approaches to understand it. This review essay discusses recent perspectives, theories, and empirical evidence on the matter, and adds a perspective of the implications of this technology and of the policy discussion it has sparked, from the perspective of developing countries’ economies. The latter is motivated by the relative scarcity of such perspectives in the current public debate, which seems to have minimized the potential effects on the interaction of labor markets between developing and developed countries, and on the potentially different within-country effects at different levels of development.